Prediction of pathological nodal involvement by CT‐based Radiomic features of the primary tumor in patients with clinically node‐negative peripheral lung adenocarcinomas. Issue 6 (29th April 2018) - Liu, Ying; Kim, Jongphil; Balagurunathan, Yoganand; Hawkins, Samuel; Stringfield, Olya; Schabath, Matthew B.; Li, Qian; Qu, Fangyuan; Liu, Shichang; Garcia, Alberto L.; Ye, Zhaoxiang; Gillies, Robert J.
Abstract : Purpose: The purpose of this study was to investigate the potential of computed tomography (CT) based radiomic features of primary tumors to predict pathological nodal involvement in clinically node‐negative (N0) peripheral lung adenocarcinomas. Methods: A total of 187 patients with clinical N0 peripheral lung adenocarcinomas who underwent preoperative CT scan and subsequently received systematic lymph node dissection were retrospectively reviewed. 219 quantitative 3D radiomic features of primary lung tumor were extracted; meanwhile, nine radiological semantic features were evaluated. Univariate and multivariate logistic regression analysis were used to explore the role of these features in predicting pathological nodal involvement. The areas under the ROC curves (AUCs) were compared between multivariate logistic regression models. Results: A total of 153 patients had pathological N0 status and 34 had pathological lymph node metastasis. On univariate analysis, fissure attachment and 17 radiomic features were significantly associated with pathological nodal involvement. Multivariate analysis revealed that semantic features of pleural retraction ( P = 0.048) and fissure attachment ( P = 0.023) were significant predictors of pathological nodal involvement (AUC = 0.659); and the radiomic feature F185 (Histogram SD Layer 1) ( P = 0.0001) was an independent prognostic factor of pathological nodal involvement (AUC = 0.73). A logistic regression model produced from combining radiomic feature and semantic feature showed the highest AUC of 0.758 (95% CI: 0.685–0.831), and the AUC value computed by fivefold cross‐validation method was 0.737 (95% CI: 0.73–0.744). Conclusions: Features derived on primary lung tumor described by semantic and radiomic could provide information of pathological nodal involvement in clinical N0 peripheral lung adenocarcinomas.